2021
DOI: 10.3390/medicina57080781
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacterial Application in Pediatric Critical Illness as Coadjuvants of Therapy

Abstract: The use of probiotics in critically ill adult and children patients has been growing exponentially over the last 20 years. Numerous factors in pediatriac intensive care unit (PICU) patients may contribute to intestinal dysbiosis, which subsequently promotes the pathobiota’s growth. Currently, lactobacillus and bifidobacterium species are mainly used to prevent the development of systemic diseases due to the subverted microbiome, followed by streptococcus, enterococcus, propionibacterium, bacillus and Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…It is a protein that reacts faster, is sensitive, easy to measure, has a short half-life, fast reaction time, and its catabolism is not affected by the inflammation type. In this study, no adverse effects were observed when taking probiotics or placebo [19][20] . Wang Y et al, Araujo GV et al concluded that the probiotics had a safety profile as most RCTs had no adverse effects.…”
Section: Discussionmentioning
confidence: 57%
“…It is a protein that reacts faster, is sensitive, easy to measure, has a short half-life, fast reaction time, and its catabolism is not affected by the inflammation type. In this study, no adverse effects were observed when taking probiotics or placebo [19][20] . Wang Y et al, Araujo GV et al concluded that the probiotics had a safety profile as most RCTs had no adverse effects.…”
Section: Discussionmentioning
confidence: 57%